VERTICAL PROFILE VARIABILITY OF TEMPERATURE AND DENSITY IN THE WATERS OF SOUTHERN SUMBAWA - Qonita, Zulfa
Based on data of the vertical temperature and salinity in the waters south of the island of Sumbawa for 15 years, an analysis of the variability vertical profiles of temperature and density is made. The data is obtained from field measurements made by PT. Newmont Nusa Tenggara by using a thermistor and Conductivity Temperature Depth (CTD). Historically, in determining the mixed layer depth, a change criterion of 1oC temperature with 10m of depth reference is used, whereas to determine the depth of the thermocline layer, the temperature gradient criteria with a depth of 0,1oC/m is used. In determining the depth of the vertical profile density, the criterion defined by Brainerd and Gregg (1995) is used where the depth of the upper limit pycnocline with matching value criteria is 0,1 kg/m3 and the lower limit value pycnocline with matching value is 0,2 kg/m3. It is concluded that the seasonal variability in the vertical profile of temperature and density in the waters south of the island of Sumbawa is influenced by the monsoon winds, while the variability of annual vertical profiles of temperature and density is influenced by the weather phenomenon El-Ni?????o Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD).In general the depth of upper threshold in the western monsoon was deeper compare to in the eastern monsoon. In general found above the thermocline depth limit (pycnocline) and the lower limit of the thermocline (pycnocline) on the west monsoon season is deeper than the east. Based on the inter-annual variations in global climate is found that the upper limit of the thermocline and piknoklin at El-Ni?????o events are generally more shallow upper limit in the waters of the thermocline and its South piknoklin Sumbawa Island with the average of the upper limit of the thermocline (pycnocline) 23-52 m (38.8 - 101.7 m) than when there is La-Ni?????a with the average of the upper limit of the thermocline (pycnocline) 42-76 m (74.7 - 139.4 m). For the lower limit of the thermocline and piknoklin in the event El-Ni?????o with the average 129-205 m (158.7 -235.6 m) and the time of the incident La-Ni?????a lower limit of the thermocline and thus pycnocline with a mean thickness of the thermocline and pycnocline on the strong El-Ni?????o be more shallow than the time of the incident La-Ni?????a. The value of IOD variability affect the depth of the upper limit and lower limit of the thermocline (pycnocline). The greater the value of IOD (+), the upper limit of the upper and lower limit of the thermocline (pycnocline) will be increasingly shallow.